The Ascent of India: From Colony to the Threshold of a Great Power - Alcalde Cardoza, Javier (2016)
India began in 1947 simultaneous processes of state-building and international positioning. Under the leadership of Nehru and Indira Gandhi, consecutively, she was able to overcome great obstacles in the way of achieving a secular and democratic state, progress economically, and manage her external environment. The end of the Cold War confronted Delhi with the need to make radical adjustments in her economic and foreign policies. India partially liberalized her economy and came closer to the U.S. These changes have left India at the doors of Great Power status. At the same time, internal forces are striving to make of India a Hindu nation.